Are Geckos Special in Sex Determination? Independently Evolved Differentiated ZZ/ZW Sex Chromosomes in Carphodactylid Geckos - Augstenová, Barbora; Pensabene, Eleonora; Veselý, Milan; Kratochvíl, Lukáš; Rovatsos, Michail (Genome biology and evolution, 2021)
Amniotes possess astonishing variability in sex determination ranging from environmental sex determination (ESD) to genotypic sex determination (GSD) with highly differentiated sex chromosomes. Geckos are one of the few amniote groups with substantial variability in sex determination. What makes them special in this respect? We hypothesized that the extraordinary variability of sex determination in geckos can be explained by two alternatives: 1) unusual lability of sex determination, predicting that the current GSD systems were recently formed and are prone to turnovers; and 2) independent transitions from the ancestral ESD to later stable GSD, which assumes that geckos possessed ancestrally ESD, but once sex chromosomes emerged, they remain stable in the long term. Here, based on genomic data, we document that the differentiated ZZ/ZW sex chromosomes evolved within carphodactylid geckos independently from other gekkotan lineages and remained stable in the genera Nephrurus, Underwoodisaurus, and Saltuarius for at least 15 Myr and potentially up to 45 Myr. These results together with evidence for the stability of sex chromosomes in other gekkotan lineages support more our second hypothesis suggesting that geckos do not dramatically differ from the evolutionary transitions in sex determination observed in the majority of the amniote lineages.
Keywords: sex determination; Animals; Phylogeny; reptiles; Sex Determination Processes; ještěři; DNA-seq; zvířata; pohlavní chromozomy; biologická evoluce; Biological Evolution; fylogeneze; Sex Chromosomes; procesy určující pohlaví; qPCR; genomics; sex chromosomes; Lizards